ERGONOMIC CONSIDERATION OF THE EFFECT OF FLOUR DUST ON PEAK EXPIRATORY FLOW RATE OF BAKERS IN ABEOKUTA, OGUN STATE - Adekunle Ibrahim MUSA; Oluseyi A. ORELAJA (Transactions of the VŠB: Technical University of Ostrava, Safety Engineering Series, 2017)
Flour dusts are one of the most harmful chemicals in the bakery industries which could lead to serious heart and lung diseases. This study investigated the effect of flour dust on Peak Expiratory Flow Rate of male bakers in Abeokuta, Ogun State, Nigeria with the relationship to the anthropometrical parameters. A total of One hundred Eighty (180) male participants were investigated, where ninety (90) participants were bakers and ninety (90) individuals as control group. The Peak expiratory flow rate (PEFR) and anthropometrical parameters of the participant were measured using mini-Wright peak flow meter (PFM 20, OMRON) and Detecto PD300MDHR (Cardinal Scale manufacturing company, USA) column scale with digital height rod was used to measure body mass [kg] and height (cm) respectively. The PEFR and anthropometrical parameters of the bakers and control groups were analysed using descriptive statistics and T-test with SPSS. The results showed that lower PEFR, 182.67 ± 16.34 L/min existed in bakers compared to 287.67 ± 17.02 L/min in the control study. The result also showed that a significant correlation exist between body mass, height and age (P < 0.01), PEFR, height (P < 0.05) and years of exposure (P < 0.01) of the bakers respectively. Furthermore, the results also showed that workers in the dusting and mixing of flour are at a risk of developing related pulmonary function impairment such as asthma. The study concluded that there is need to develop an effective intervention strategy, treatment seeking behaviour through awareness programs to prevent lung impairment diseases among the bakery workers.